Blending of reactive prepolymers to control the morphology and polarity of polyglycidol based microgels. Issue 5 (17th December 2014) - Schulte, B.; Rahimi, K.; Keul, H.; Demco, D. E.; Walther, A.; Möller, M.
Abstract : The synthesis and characterization of nanostructured multicomponent microgels with different polarities and morphologies based on polyether prepolymers are presented. Abstract : The compartmentalization of microgels is a challenging task for synthetic polymer chemistry. Although the complexation with low molecular weight compounds or the use of microfluidic techniques offer attractive possibilities for other length scales, it is difficult to implement compartments in the mesoscale range of 10–100 nm. Herein we show how simple blending of reactive prepolymers is suitable to design new microgel morphologies with tailored compartments. We use poly(EEGE)- block -poly(AGE) as crosslinkable, pro-hydrophilic prepolymer in blends with varying amounts of crosslinkable, yet hydrophobic poly(THF- stat -AllylEHO) or inert and hydrophobic polystyrene, and crosslink the allyl functional prepolymer(s) in a thiol-ene click-type reaction after miniemulsification. Our strategy shows how arrested versus free nanophase separation can be used to control easily the morphology and polarity of microgel particles.